2012
DOI: 10.1097/jes.0b013e3182571e2c
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Remodeling and the Exercise Physiology of Fish

Abstract: Fish muscle responds to aerobic exercise training and cold acclimation with a more aerobic muscle phenotype than mammalian muscle but through both conserved and distinct molecular events. Differences from mammals in exercise metabolism and diversity in protein isoforms suggest that the regulation of muscle fuel use is more complex in fish. This review considers fish as powerful models for exercise and muscle physiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Does terrestrial exercise in fishes (e.g. mudskippers on a treadmill; Jew et al, 2013) lead to the same training effect as observed with swimming (McClelland, 2012)? Do fishes need to balance trade-offs when adjusting locomotor performance for aquatic versus terrestrial locomotion and, if so, how do lag times in the induction and reversal of these responses influence the scope of plasticity in fishes with different amphibious habits ( Fig.…”
Section: Buoyancy Gravity and Movement On Landmentioning
confidence: 96%
“…Does terrestrial exercise in fishes (e.g. mudskippers on a treadmill; Jew et al, 2013) lead to the same training effect as observed with swimming (McClelland, 2012)? Do fishes need to balance trade-offs when adjusting locomotor performance for aquatic versus terrestrial locomotion and, if so, how do lag times in the induction and reversal of these responses influence the scope of plasticity in fishes with different amphibious habits ( Fig.…”
Section: Buoyancy Gravity and Movement On Landmentioning
confidence: 96%
“…Data: Swim training generally increases (Davison 1997;Anttila et al 2006), but may have no effect (e.g., Lemoine et al 2010;Martin-Perez et al 2012;McClelland 2012;He et al 2013;Magnoni et al 2013). Dependent on muscle fiber-type (reviewed by Davison 1997).…”
Section: Datamentioning
confidence: 99%
“…Many researchers have hypothesized that exercise could potentially represent a natural, noninvasive, and economical approach to improve fish growth (Schwebel, 2017). With extensive research and experimentation, fish have become a powerful model for exercise training and muscle development (McClelland, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, white fibers may also be recruited to a lesser extent (Palstra & Planas, 2011). Since there is such a clear anatomical separation between the muscle masses, fiber type-specific responses to exercise can be determined more easily (McClelland, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation